Factors inherent to the nursery, growing and finishing phases influence biomarkers of muscle activity, protein metabolism and oxidative stress in pigs - Bezerra, Belise Maria Oliveira (2016)
ABSTRACT. Bezerra B.M.O., de Oliveira A.M.A., Silva C.V.O., Andrade T.S., Guedes R.F. de M., Lemos J.C., Evangelista J.N.B. & Nunes-Pinheiro D.C.S. [Factors inherent to the nursery, growing and finishing phases influence biomarkers of muscle activity, protein metabolism and oxidative stress in pigs.] Fatores inerentes às fases de creche, crescimento e terminação influenciam marcadores da atividade muscular, do metabolismo proteico e do estresse oxidativo em suínos. Revista Barasileira de Medicina Veterinária, 38(4):371-376, 2016. Programa de Pós-Graduação em Ciências Veterinárias, Faculdade de Veterinária, Universidade Estadual do Ceará, Av. Dr. Silas Munguba, 1700, Campus do Itaperi, Fortaleza, CE 60714-903, Brasil. E-mail: belise_oliveira@hotmail.comBrazilian pig farming is mainly characterized by an intensive system, and its creation phases are marked by specific conditions. However, there is a few studies about the influence of those conditions on the physiology of the animal. The objective of this study was to evaluate biochemical parameters and biomarkers of oxidative stress in pigs at the nursery, growing and finishing phases. Pigs (n=14), both sexes, Landrace x Large White x Duroc, healthy, housed in commercial farm were used. The animals were submitted to blood collections on days: D1 = 71; D2 = 74; D3 = 116; D4 = 151 for evaluation.  Results were expressed as mean ± sd (p≤0.05). AST values had greater in younger pigs (p≤0.05). CK values were greater at the end of the nursery phase and in the finishing phase (p≤0.05). These two parameters were positively correlated. Creatinine, urea and albumin values in experimental pigs were positively correlated and they were higher in pigs at the end of the finishing phase (p≤0.05). Markers of oxidative stress, nitric oxide and MDA, were greater in pigs in the early growth stage and out the nursery phase, respectively (p≤0.05). It was concluded that factors associated to nursery, growing and finishing phases can influence biomarkers of muscle activity, protein metabolism and oxidative stress. It is expected that this data will contribute to the understanding of physiology in swine breeding systems.